The Clue Of The Dancing Puppet - Keene Carolyn; Carolyn Keene (New York Carolyn Keene, 1962)
follows Nancy, Bess, and George investigating a life-size puppet haunting the Van Pelt estate
Keywords: refers to the 39th volume in the Nancy Drew Mystery Stories series, published in 1962.; The most common, direct interpretations are related to independence, authenticity, and cautionary tales